Transients in power systems - Van der Sluis, Lou (Wiley, 2001)
Covering the fundamentals of electrical transients, this book should equip readers with the skills to recognise and solve transient problems in power networks and components. Starting with the basics of transient electrical circuit theory, and moving on to discuss the effects of power transience in all types of power equipment, it provides insight into this important field. Recent advances in measurement techniques, computer modelling and switchgear development are given comprehensive coverage for the first time. An electromagnetic transients calculation program is included and should prove valuable to both students and engineers in the field.